3D chitosan scaffolds impair NLRP3 inflammasome response in macrophages. (June 2019) - Vasconcelos, Daniela P.; de Torre-Minguela, Carlos; Gomez, Ana I.; Águas, Artur P.; Barbosa, Mário A.; Pelegrín, Pablo; Barbosa, Judite N.
Graphical abstract: Abstract: Chitosan (Ch) is used in different biomedical applications to promote tissue repair. However, tissue injury caused by biomaterial implantation lead to the release of danger signals that engage different inflammatory pathways on the host. Different implanted materials activate the inflammasome leading to the modulation of the immune response. Here we have studied how macroscopic biomaterials, Ch scaffolds with different chemical composition: 4% or 15% degree of acetylation (DA) modulate the activation of the NLRP3 inflammasome in vitro. For that, we assessed the NLRP3 inflammasome in bone marrow derived mouse macrophages (BMDM) and human macrophages cultured within 3D Ch scaffolds. We found that both Ch scaffolds did not trigger the NLRP3 inflammasome activation in macrophages. Furthermore, BMDMs and human macrophages cultured in both Ch scaffolds presented a reduction in the number of apoptosis-associated speck-like protein containing a caspase activating recruitment domain (ASC) specks and in IL-1β release upon classical NLRP3 inflammasome stimulation. We also found a decrease in proIL-1β in BMDMs after priming with LPS when cultured in Ch scaffolds with DA 4% DA after priming with LPS when compared to Ch scaffolds with 15% DA or to macrophages cultured in cell-culture plates. Our results shows that 3D Ch scaffolds with different DA impair NLRP3 inflammasome priming and activation. Statement of Significance: In this research work we have assessed the role of the NLRP3 inflammasome in the macrophage response to 3D chitosan scaffolds with different degrees of acetylation (DA). To our knowledge this is the first work that demonstrates the modulatory capacity of 3D porous chitosan scaffolds in the NLRP3 inflammasome activation, because our results show that Ch scaffolds impair NLRP3 inflammasome assembly in macrophages. Interestingly, our results are in contrast with studies reported in the literature that indicate that chitosan is a powerful activator of the NLRP3 inflammasome in nanoscale chitosan products. Our studies that were performed in large scale chitosan scaffolds, stress out that the process of phagocytosis is pivotal in inflammasome assembly and activation, are rather important since they clearly illustrate the different role of the inflammasome in the biological response to large scale and nanoscale biomaterials.